2011
DOI: 10.1038/npp.2011.217
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Blockade Attenuates the General Incentive Motivational Effects of Noncontingently Delivered Rewards and Reward-Paired Cues Without Affecting Their Ability to Bias Action Selection

Abstract: Environmental cues affect our behavior in a variety of ways. Despite playing an invaluable role in guiding our daily activities, such cues also appear to trigger the harmful, compulsive behaviors that characterize addiction and other disorders of behavioral control. In instrumental conditioning, rewards and reward-paired cues bias action selection and invigorate reward-seeking behaviors, and appear to do so through distinct neurobehavioral processes. Although reward-paired cues are known to invigorate performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…Given dopamine's well-established involvement in the response-invigorating influence of reward-paired cues (Dickinson et al, 2000;Lex and Hauber, 2008;Ostlund and Maidment, 2012;Wassum et al, 2011Wassum et al, , 2013, such an interaction may be at least partially responsible for mediating the disruptive effect of mecamylamine reported here. However, this would not explain the similar disruption produced by scopolamine, given that it and other muscarinic receptor antagonists tend to facilitate dopamine signaling by blocking acetylcholine autoreceptor activity (Cachope et al, 2012;Chapman et al, 1997;Di Giovanni and Shi, 2009).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Given dopamine's well-established involvement in the response-invigorating influence of reward-paired cues (Dickinson et al, 2000;Lex and Hauber, 2008;Ostlund and Maidment, 2012;Wassum et al, 2011Wassum et al, , 2013, such an interaction may be at least partially responsible for mediating the disruptive effect of mecamylamine reported here. However, this would not explain the similar disruption produced by scopolamine, given that it and other muscarinic receptor antagonists tend to facilitate dopamine signaling by blocking acetylcholine autoreceptor activity (Cachope et al, 2012;Chapman et al, 1997;Di Giovanni and Shi, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…Both families of receptors are highly expressed in brain areas implicated in instrumental learning and performance, including the striatum, prefrontal cortex, and amygdala (Goldberg et al, 2012;Leslie et al, 2013;Thiele, 2013). Acetylcholine is also known to be involved in regulating dopamine signaling (Cachope et al, 2012;Chapman et al, 1997;Di Giovanni and Shi, 2009;Threlfell et al, 2012), a neuromodulator that has been more directly implicated in motivated behavior and is known to underlie the response-invigorating influence of rewardpaired cues on reward-seeking behavior (Dickinson et al, 2000;Lex and Hauber, 2008;Ostlund and Maidment, 2012;Wassum et al, 2011Wassum et al, , 2013. While acetylcholine has been implicated in various aspects of reward-motivated behavior (Mendez et al, 2012;Pratt and Kelley, 2004;Ragozzino et al, 2009), much remains unknown about its specific contributions to action selection.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting hypothesis posits that Pavlovian predictions of outcomes (rewards) underpin some types of instrumental-based control of behavior (1). One example is Pavlovian-to-instrumental transfer, in which Pavlovian cues actually modify instrumental responses (38,39). We have previously shown that vrDD-DS mice are similar to vrDD-VS mice in their ability to learn an instrumental lever-press response (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…46 Additionally, mice without alpha7 nAChRs exhibited normal physical effort motivation but impaired reward-associative learning, 87 despite such mice exhibiting normal learning in aversively motivated environments. 88 Other differences include the need of the dorsal striatum in rats performing an effort-based decision-making task 89,90 but not in the PRBP. 91 Future studies using specific cross-species tests and manipulations may solidify the neuromechanisms mediating these specific behaviors in both humans and rodents for as yet there remain too few studies for a complete understanding.…”
Section: Neuromechanismsmentioning
confidence: 99%